Perspectives of applied collaborative sport science research within professional team sports - Harper, L. D.; Jones, B.; Perry, J.; Barnes, C.; Towlson, C. (European Journal of Sport Science, 2019)
The purpose of the study was to examine the perspectives of both academics and practitioners in relation to forming applied collaborative sport science research within team sports. Ninety-three participants who had previously engaged in collaborative research partnerships within team sports completed an online survey which focused on motivations and barriers for forming collaborations using blinded sliding scale (0-100) and rank order list. Research collaborations were mainly formed to improve the team performance (Academic: 73.6 ± 23.3; Practitioner: 84.3 ± 16.0; effect size (ES = 0.54), small). Academics ranked journal articles` importance significantly higher than practitioners did (Academic: Mrank = 53.9; Practitioner: 36.0; z = -3.18, p = .001, p < q). However, practitioners rated one-to-one communication as more preferential (Academic: Mrank = 41.3; Practitioner 56.1; z = -2.62, p = .009, p < q). Some potential barriers were found in terms of staff buy in (Academic: 70.0 ± 25.5; Practitioner: 56.8 ± 27.3; ES = 0.50, small) and funding (Academic: 68.0 ± 24.9; Practitioner: 67.5 ± 28.0; ES = 0.02, trivial). Both groups revealed low motivation for invasive mechanistic research (Academic: 36.3 ± 24.2; Practitioner: 36.4 ± 27.5; ES = 0.01, trivial), with practitioners have a preference towards `fast` type research. There was a general agreement between academics and practitioners for forming research collaborations. Some potential barriers still exist (e.g. staff buy in and funding), with practitioners preferring `fast` informal research dissemination compared to the `slow` quality control approach of academics